The Meaning of Lengger Dancers' Beauty in Wonosobo Regency - Utiya Ni'matul Kamila; Gunawan (Pusat Studi Gender Universitas Jember, 2025)
Beauty is a concept that is constructed and interpreted differently in every society. In performing arts, beauty becomes ani mportant part that influences the image of a dancer. This study aims to describe how dancers and the community interpret he beauty of lengger dancers in Wonosobo Regency. This study uses a qualitative method with a phenomenologicala pproach. Data were obtained through in-depth interviews, observation and documentation. The results of the study showt hat the meaning of beauty of lengger dancers from the community and lengger dancers themselves have differences. The community tends to interpret beauty visually, while dancers interpret it more broadly and specifically. Beauty will be more directed at inner beauty, flexibility in dancing, the ability to combine makeup and costumes and beauty through spirituala ctivities that are carried out. This meaning becomes a standard of beauty and develops in society. From this standard, a myth of beauty is constructed that becomes a control and is restrictive. The myth that develops makes lengger dancers manifest their beautiful appearance through the behavior they do. This is shown by lengger dancers such as taking care of themselves, honing their dance skills, using makeup according to developments and performing various special rituals.